CAREER PLANNING EDUCATION FOR NABILAH BATAM ISLAMIC HIGH SCHOOL STUDENTS - Ita Mustika; Sarmini Sarmini; Mulyadi Mulyadi; Ferdilla Ferdilla (International Journal of Engagement and Empowerment, 2022)
Career planning for students is essential to develop in support of the desired goals. Therefore, students are expected to have a career plan according to their talents, interests, level of intelligence, and life values to make it easier for students to plan a career. This study aims to improve career planning skills for high school students (SMA). In this activity, several methods were used, including the lecture method, the discussion, and planning method, the question and answer method, and the evaluation method. The results of this service indicate that 62 students generally show an increase in knowledge about self-understanding, self-preparation, introduction to the world of work, and future planning